A Phylogenetic Assessment of Flatfish (Order Pleuronectiformes) Intrarelationships Based on Molecular Evidence - Byrne, Lisa (Université d'Ottawa / University of Ottawa, 2018)
The fish order Pleuronectiformes (flatfishes) include over 800 fish species, and are generally considered to be monophyletic. Phylogenetic relationships within the order remain largely unresolved, particularly for the Paralichthyidae, a very poorly defined family. In addition to the lack of consensus on intrarelationships within this order, flatfish diversification patterns are still poorly understood. Here we want to test the hypothesis that (i) a densely sampled phylogenetic tree will help to unravel the phylogenetic relationships within flatfish, and (ii) that the formation of the Isthmus of Panama has played a role in the diversification of flatfish, following their distribution in both oceans, Atlantic and Pacific. Maximum likelihood and Bayesian analyzes were performed on a dataset consisting of nine mitochondrial and nuclear loci on a set of 309 flatfish species. The heterogeneity of substitution rates, known to cause phylogenetic errors in large multigene alignments, can be corrected by data partitioning, or by using heterogeneous site models. Very few studies have compared the effects of using these approaches. We present a robust phylogenetic tree with different heterogeneous and well-supported models, and the intraordinal relationships of flatfish are discussed in light of these results. We present evidence for three new suborders within the flatfishes. The monophyletic status of most families is corroborated. The family Paralichthyidae and the family Poecilopsettidae were found to be polyphyletic. Heterogeneous models have not been able to solve the deeper relationships between flatfish. We also show that flatfish diversification occurred in a few families in at least two stages, related to distinct geological events.
Keywords: Molecular; Phylogenetics; Flatfish; Systematics; Vicariance; Isthmus of Panama; Pleuronectiformes